Social Support Attainment of Older Adults Living in a Flood-Prone Community - Arlene Supremo; Sillmark Bacason; Alpha Issa Christianne Abegonia; Louverille Bacason (Jurnal Ners, 2020)
Introduction: A flood, a catastrophic phenomenon often experienced by many, brings destruction to property and livelihood. This kind of event renders access to basic services difficult. During times of floods, older adults need additional social support, from family, friends, relatives, or significant others. The aim of this study was to investigate the level of attainment of social support of older adults during periods of floods and periods without floods.Methods: A descriptive quantitative research design was used. Purposive sampling was utilized to reach the population sample of 126 elderly respondents. They were interviewed face-to-face in their homes using a modified questionnaire. To analyze the data, descriptive statistics and mean scores were used.Results: 126 older adults participated in the research study. Most older adults strongly agreed that they received social support during periods of floods (with a mean score of 4.40) and without floods (with a mean score of 4.39).Discussion: Social support was extended to older adults both during times of floods and without floods. The support they received from people who were special to them maintained their health and well-being.